2018
DOI: 10.1016/j.cell.2018.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Profound Tissue Specificity in Proliferation Control Underlies Cancer Drivers and Aneuploidy Patterns

Abstract: Genomics has provided a detailed structural description of the cancer genome. Identifying oncogenic drivers that work primarily through dosage changes is a current challenge. Unrestrained proliferation is a critical hallmark of cancer. We constructed modular, barcoded libraries of human open reading frames (ORFs) and performed screens for proliferation regulators in multiple cell types. Approximately 10% of genes regulate proliferation, with most performing in an unexpectedly highly tissue-specific manner. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 49 publications
17
164
4
Order By: Relevance
“…We chose gain-of-function perturbations as they are an effective way of exploring cell states (5,(36)(37)(38), and with CRISPRa are now feasible to implement systematically for quantitative interaction studies. From a previous genome-wide CRISPRa screen, we selected 112 hit genes whose activation enhanced or retarded growth of K562 cells ( Fig.…”
Section: Results: a Crispra Fitness-level Genetic Interaction Mapmentioning
confidence: 99%
“…We chose gain-of-function perturbations as they are an effective way of exploring cell states (5,(36)(37)(38), and with CRISPRa are now feasible to implement systematically for quantitative interaction studies. From a previous genome-wide CRISPRa screen, we selected 112 hit genes whose activation enhanced or retarded growth of K562 cells ( Fig.…”
Section: Results: a Crispra Fitness-level Genetic Interaction Mapmentioning
confidence: 99%
“…Overall, our results indicate that differences of chromosome arm-wide gene expression levels in normal human tissues are enhanced by the acquisition of aneuploidies in the cognate tumors, suggesting a non-oncogenic, tissue-specific physiological basis for clonal expansion. 24 have demonstrated that the inclusion of tissue-specific growth promoting genes strengthens the correlation between chromosome arm loss/gain ratios and the proliferation-driving capability of each chromosome-arm in breast and pancreatic cancers. A general, yet not tissue-specific, role of copy number alterations and metabolic selection pressure was reported by Graham and colleagues 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Sack and colleagues (23) have demonstrated that the inclusion of tissue-specific growth promoting genes strengthens the correlation between chromosome arm loss/gain ratios and the proliferation-driving capability of each chromosome-arm in breast and pancreatic cancers, yet, other aspects of tumor biology, such as immune evasion, invasion and metastasis have to be considered. Graham and colleagues report a general, yet not tissue-specific, role of copy number alterations and metabolic selection pressure (24).…”
mentioning
confidence: 99%
“…Noticeably, cancers of distinct anatomical origins exhibit quite different profiles of genomic and epigenetic anomalies . Recent work, based on human open reading frame library screening in three different cell types to identify proliferation drivers, elegantly showed the existence of a tissue‐specific selection for gains of function and loss of tumor suppressors …”
Section: Introductionmentioning
confidence: 99%
“…6 Recent work, based on human open reading frame library screening in three different cell types to identify proliferation drivers, elegantly showed the existence of a tissue-specific selection for gains of function and loss of tumor suppressors. 7 In breast cancer, molecular subtypes were defined on the basis of RNA expression, as well as of genomic anomalies and DNA methylation differences. [8][9][10][11] Although definitive proof remains missing, it is generally proposed that the genetic and epigenetic differences in different breast tumor subtypes are dictated by distinct cell types of origin.…”
Section: Introductionmentioning
confidence: 99%